Ethnomathematics: Exploration of mathematical concepts in Riau Malay special food - Suripah; Marsigit Marsigit; Rusli Rusli (STKIP PGRI Banjarmasin, 2021)
The development of an increasingly advanced technology is one of the causes for cultural values to fade and be marginalized. Therefore, exploration of culture is needed to support the sustainability of mathematics learning. this study aims to explore the mathematical concepts found in Riau Malay specialties and their application in mathematics learning. this research is a qualitative study using an ethnographic approach. The instrument used are human instrument. The researcher communicates directly with the object of research and participate actively in data collection, either by means of literature study, interview, observation, and documentation. The data analysis technique was carried out by means of data reduction, presentation, analysis, and data exposure. The results of this study are in the form of mathematical concepts found in Riau Malay specialties, namely: point, line, bowstring, triangle, rectangle, regular, octagon, circle, rectangular pyramid, beam, and congruence. Mathematical concepts found in Riau Malay specialties can be used to introduce and understand mathematical concepts in learning through local wisdom.